The Mental Health Impacts of Wildfire Exposure: A Scoping Review of the Quantitative Evidence - Katharine A. Teigen; David M. Coomes; Amruta Nori-Sarma; Joan A. Casey (Current Environmental Health Reports, 2026)
Wildfires are increasing in frequency and intensity worldwide, with growing evidence linking wildfire exposure to adverse mental health outcomes. This scoping review aimed to summarize and critically assess the existing quantitative literature on wildfire-related mental health impacts. We searched PubMed, Web of Science, and Google Scholar to identify studies published between 2000 and 2025, which we analyzed to understand how wildfires were investigated, evaluate how exposure was measured, assess mental health outcomes, and identify persistent gaps in the literature. Of 251 unique manuscripts identified, 85 met inclusion criteria. Studies were primarily conducted in Australia (34.1%), Canada (31.8%), and the United States (29.4%), with limited representation from Greece, Italy, Israel, South Korea, and Spain. Exposure assessment methods varied widely, where 21.2% of studies considered everyone uniformly exposed. Other exposure assessment methods used were evacuation status, questionnaires, researcher-ascribed loss severity, and spatio-temporal proximity. Depression was the most frequently studied outcome (evaluated in 58.5% of studies), followed by post-traumatic stress disorder (52.9%) and anxiety (48.2%). Other outcomes included insomnia, suicidality, substance use, and resilience. Most studies reported elevated adverse mental health following wildfires, though findings varied. Multiple aspects of wildfire exposure, including direct exposure, seeing flames or smoke, and being evacuated were consistently associated with adverse mental health outcomes. Limitations in the literature included non-standardized exposure assessments, limited geographic diversity, and a shortage of rigorous epidemiologic study designs. Addressing these gaps is essential to improving understanding of wildfire-related mental health impacts and informing public health responses.